The changing nature of the academic role in science. - Ross, Pauline (Australia. Department of Education, 2019)
This fellowship report aims to reconceptualise the academic role in the sciences, create a dialogue between academic groups from senior leaders in disciplinary researches and the learning and teaching community to define the current and future shape of an academic role in science. It also presents an evaluation framework to evaluate academic teaching in the sciences. It describes the fellowship outputs including an analysis of the academic role as described in data from the Department of Education and Training, a summary of the description of academic roles as set out in the enterprise bargaining agreements and what is valued as evidence of quality in the education- or teaching-focused academic role as outlined in promotion criteria and the learning and teaching community. Interviews, insights and understandings on the education/teaching focused role in science were conducted with a range of academics across a range of institutions. This included interviews with senior leaders in disciplinary research and the learning and teaching community. An evaluative framework (professional development framework) and a set of enabling tools to empower education/teaching focused academics to make an impact in their career and more explicitly enable early- to mid-career academics in education- or teaching-focused roles to evidence their impact and create a career trajectory in science. Ten major themes of concerns emerged about the differentiating academic role in science. These were categorised as value, expertise, scholarship, reputation, funding, progress and promotion, research, community and connections, view of students, and metrics and merit. The challenge for an education/teaching focused academic is to retain research currency. To address many of the challenges facing the academic workforce in science, among other solutions a productive partnership between education/teaching focused academics and disciplinary and education researchers was proposed.